The role of imbalance of protection and aggression factors in gastric juice in the development of candidiasis of mucous tunic of the upper part of digestive tract - Кушніренко, Інесса Василівна (ScienceRise: Medical Science, 2016)
Research is devoted to the study of endogenous factors that would explain conditions of the spread of Candida albicans infection into the distal parts of digestive tract and their possible connection with comorbid pathology of thyroid gland. The aim of research is the study of pepsin, glycoproteins, hexosamines, fucose, sialic acid level in the gastric juice of patients with candidiasis of mucous tunic of the upper section of digestive tract. Methods. There were examined 116 patients, who were divided into three groups according to the results of microbiological examination: 1 group – 57 patients with IV degree of massivity of Candida fungi seeding that is with oropharyngeal candidiasis (OPC) and surface fungi growth the in mucous tunic of digestive tract and/or stomach; 2 group – 42 patients with invasive Candida fungi growth in the mucous tunic of digestive tract and/or stomach; 3 group – 17 patients without OPC and fungi growth in biopsy material. The subgroup 1А included 12 patients of the 2 group with surface fungi growth in biopsy materials of digestive tract and/or stomach. In the stomach content was determined pepsin, glycoproteins, sialic acids, fucose, hexosamines concentration. The control group included 20 practically healthy persons. The ultrasound examination of thyroid gland was carried out. Statistical analysis was realized using Pirson’s χ2 criterion, Fisher’s distinct criterion (F), Student’s t-criterion. Correlation analysis was carried out using Pirson’s correlation coefficient (r) for parametric values and Spearmen’s one (ρ) for nonparameric values. Results. According to the results of research was detected the rise of hexosamines synthesis in patients with candidiasis of 1 and 2 group comparing with patients without candidiasis (р<0,001) and (p<0,01), respectively, and increase of glycoproteins in patients with Candida invasion in mucous tunic comparing with patients with surface fungi growth (р<0,05). The decrease of fucose was typical for patients of all groups comparing with control, but the changes of indices of the main structural components of mucin at the expense of its decrease were more expressed in patients with fungi invasion in the mucous tunic that was proved by their direct correlations with surface and invasive Candida albicans growth in the stomach body. Structural changes such as hyperplasia of thyroid gland and nodular goiter that were detected in one third of examined patients with candidiasis of mucous tunic were associated with indices of mucin structural degradation. Conclusions. In patients with candidiasis of mucous tunic of the upper part of digestive tract was revealed imbalance in the ratios of structural components that was formed at the expense of decrease of hydrophobic final fucose component. Negative influence of mucin structural degradation at the expense of fucose decrease on the course of candidiasis of mucous tunic of the upper part of digestive tract is proved by the direct correlation with indices of Candida albicans growth of the mucous tunic of stomach body according to the results of microbilogical study of biopsy materials. The direct correlation between indices of ratios glycoprotein/fucose and hexosamines/fucose and structural changes of thyroid gland such as hyperplasia and nodular goiter that were more often revealed in patients with candidiasis of mucous tunic of the upper part of digestive tract need the further study